2014
DOI: 10.1371/journal.pone.0096893
|View full text |Cite
|
Sign up to set email alerts
|

The Crude Skin Secretion of the Pepper Frog Leptodactylus labyrinthicus Is Rich in Metallo and Serine Peptidases

Abstract: Peptidases are ubiquitous enzymes involved in diverse biological processes. Fragments from bioactive peptides have been found in skin secretions from frogs, and their presence suggests processing by peptidases. Thus, the aim of this work was to characterize the peptidase activity present in the skin secretion of Leptodactylus labyrinthicus. Zymography revealed the presence of three bands of gelatinase activity of approximately 60 kDa, 66 kDa, and 80 kDa, which the first two were calcium-dependent. These three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 65 publications
0
11
0
1
Order By: Relevance
“…It is known that fragments derived from active peptides can be found in the skin secretion of frogs and, in particular, it was shown that the crude skin secretion of Leptodactylus labyrinthicus is rich in metallo and serine peptidases [49]. The peptide sequences investigated here present 100% homology from residues 1 to 22 (ocellatin-LB1 primary structure), ocellatin-LB2 carries an extra Asn and ocellatin-F1 extra Asn-Lys-Leu residues.…”
Section: Resultsmentioning
confidence: 86%
“…It is known that fragments derived from active peptides can be found in the skin secretion of frogs and, in particular, it was shown that the crude skin secretion of Leptodactylus labyrinthicus is rich in metallo and serine peptidases [49]. The peptide sequences investigated here present 100% homology from residues 1 to 22 (ocellatin-LB1 primary structure), ocellatin-LB2 carries an extra Asn and ocellatin-F1 extra Asn-Lys-Leu residues.…”
Section: Resultsmentioning
confidence: 86%
“…fallax, Krintler, 1986), and the dermal glands of several species are known to produce defensive skin secretions (Cei et al, 1967), including antimicrobial peptides and other protein toxins found in L. fallax (Rollins-Smith et al, 2005;King et al, 2005a), L. labyrinthicus (Libério et al, 2014), L. laticeps (Conlon et al, 2009), L. latrans (Nascimento et al, 2004(Nascimento et al, , 2007Leite et al, 2010), L. pentadactylus (Habermehl, 1981;Barlow, 1998;King et al, 2005b;Limaverde et al, 2009;Sousa et al, 2009), L. syphax (Dourado et al, 2007). Similarly, the foam nests of L. vastus possess a novel surfactant protein (Hissa et al, 2008(Hissa et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The skin of frogs also contains many anti-microbial peptides [125], including several FLPs [126]. Finally, frog skin also contains numerous peptidases [127]. Thus, it seems that unless the nervous system were internal to the epidermis, the multiple FLPs in both neurons and skin cells, multiple FLP receptors on neurons, and multiple peptidases produced by skin cells could all interfere with both neural signalling and epithelial-microbial signalling in frogs.…”
Section: Could Microbes Have Played a Role In Internalization Of Nervmentioning
confidence: 99%